Discussion about the Factors that Affect the Efficiency of Foreign Students in Reading Chinese Text - Charoensenee, Apiradee (Journal of Sinology (วารสารจีนวิทยา), 2009)
Reading is a complicated process of communication between the writer and the reader. It is also an important method to learn about some new knowledge and obtain some new information. Reading always has an important part either in language teaching or in practical language using. In reading a foreign language text, we cannot achieve as high efficiency as in reading a mother language text, especially in reading Chinese texts. This is because Chinese language has its special nature. The structure of its vocabulary and grammar are different from other languages. For this reason, these are important factors that affect foreigners in reading Chinese texts. The other factors are about the background knowledge and the ability in logic thinking of the students themselves.